Hubungan Beban Kerja Mental, Usia, dan Masa Kerja dengan Stres Kerja pada Pegawai Kantor Bea Cukai Surakarta - Hapsari, Kania Vita; Lestantyo, Daru; Ekawati, Ekawati (Jurnal Kesehatan Masyarakat, 2023)
Customs is an institution that has the task of protecting vital elements of the country by performing specific supervision. The heavy demand of workload for customs employee can potentially lead to them suffering from work stress. This study sought to examine how work stress in Surakarta Customs employees related to factors including mental workload, age, and working period. The OSI-RTM and NASA-TLX questionnaires were used in a cross-sectional approach as part of the research's analytical observational method. Respondents were taken using the proportionate stratified random sampling technique with a total of 60 people. The study obtained data that 51 respondents (85%) experienced mild stress and 9 others (15%) experienced moderate stress. From the testing performed with the Rank-Spearman correlation analysis obtained the results of the significance values namely mental workload (p=0,002 < 0,05; r=0,398), age (p=0,242), and working period (p=0,627). It can then be stated that there is a reasonably strong relationship between mental workload and work stress, however there is no relationship between age and working period with work stress. Taking this into consideration, the office can provide training according to the necessary competence, disperse the portion of the workload according to employee’s ability, and play music in a short period of time. While employees can do time out to calm their minds.